2014
DOI: 10.1159/000368355
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin Aggravates Cardiopulmonary Bypass-Induced Gastric Mucosal Ischemia

Abstract: Background/Aim: Upper gastrointestinal bleeding (UGIB) is one of the most frequent gastrointestinal complications after cardiac surgery with cardiopulmonary bypass (CPB). Endothelin expression and microcirculatory dysfunction have been shown to be involved in UGIB. The aim of this study was to analyze the effect of vasopressin during CPB on the gastric mucosal microcirculation and the involvement of the endothelin system. Methods: Eighteen pigs were randomized into three groups (n = 6 each): group I = sham, gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
(53 reference statements)
1
6
0
Order By: Relevance
“…In addition porcine models show that gastric blood flow is decreased with cardiopulmonary bypass. These effects were exacerbated by the addition of AVP . Porcine models showed similar results in the rectosigmoidal mucosa with decreased microvascular blood flow .…”
Section: Methodsmentioning
confidence: 65%
See 1 more Smart Citation
“…In addition porcine models show that gastric blood flow is decreased with cardiopulmonary bypass. These effects were exacerbated by the addition of AVP . Porcine models showed similar results in the rectosigmoidal mucosa with decreased microvascular blood flow .…”
Section: Methodsmentioning
confidence: 65%
“…These effects were exacerbated by the addition of AVP. 40 Porcine models showed similar FIGURE 4 Summary of findings of AVP versus placebo or catecholamines in adult CV patients that studied hemodynamics. AKI, acute kidney injury; AVP, arginine vasopressin; CABG, coronary artery bypass grafts; CI, cardiac index; CO, cardiac output; CPB, cardiopulmonary bypass; CVP, central venous pressure; LOS, length of stay; LVAD, left ventricular assist device; MAP, mean arterial pressure; MI, myocardial infraction; NE, norepinephrine; OHT, orthotopic heart transplant, PAP, pulmonary artery pressure; PCWP, pulmonary capillary wedge pressure; PVR, pulmonary vascular resistance; SV, stroke volume; SVR, systemic vascular resistance; UOP, urine output results in the rectosigmoidal mucosa with decreased microvascular blood flow.…”
Section: Adverse Effectsmentioning
confidence: 88%
“…Vasopressin has a wide range of dose-dependent physiologic effects on the cardiovascular system, arguably by increasing vascular tone and improving inotropy. Moreover, it does so without directly increasing myocardial oxygen demand or heart rate, although changes in those parameters may be indirectly induced (3,5,6,(8)(9)(10)(11)(12)(13)(14). The virtues of the drug are not merely restricted to the effects on the vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for avoiding enteral feeding may relate to the severity of the patient's baseline clinical condition rather than to the use of AVP, especially as most AVP users felt AVP was a second-line medication. Porcine models have shown a decrease in blood flow in the gastric mucosa after cardiopulmonary bypass, exacerbated by the use of AVP ( 9 , 22 ), which could pose a theoretical risk of necrotizing enterocolitis. However, Alten et al reported no cases of necrotizing enterocolitis and adequate tolerance of enteral feeds in all patients with early initiation of AVP after cardiovascular bypass surgery ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the study cohort was relatively small and further investigations are necessary to verify these findings. The same investigators found vasopressin to reduce blood flow in the superior mesenteric artery and in the rectosigmoidal mucosa, and adversatively improved distal jejunal microvascular blood flow, which underlines the ambiguity of the vasopressors’ effects [22]. …”
Section: Commentmentioning
confidence: 99%